2016
DOI: 10.1097/pas.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Fumarase-deficient Uterine Leiomyomas

Abstract: Loss-of-function germline mutations in the fumarase (FH)-gene of the Krebs cycle characterize hereditary leiomyomatosis and renal cell cancer (HLRCC)-syndrome. Fumarase (FH)-deficiency can be diagnosed by the loss of immunohistochemical expression. In this study, we investigated the occurrence and clinicopathologic features of FH-deficient uterine smooth muscle tumors (SMTs). A total of 1583 uterine and 157 non-uterine SMTs were examined using a polyclonal FH antibody and automated immunohistochemistry, and 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 23 publications
10
42
0
2
Order By: Relevance
“…Although somatic FH mutations were identified in six of the FH-deficient leiomyomas, germline testing revealed normal FH status in five (unsuccessful in the sixth). Similarly Miettinen et al 38 reported that 5% of the uterine smooth muscle tumors analyzed (n=1583) were FH-deficient by immunohistochemistry with most (79%) being leiomyomas with bizarre nuclei. They noted that while similar histologic features were often seen in both FH-deficient and FH-proficient leiomyomas with bizarre nuclei those that were FH-deficient were more likely to have staghorn vessels, prominent eosinophilic nucleoli, and perinucleolar halos.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although somatic FH mutations were identified in six of the FH-deficient leiomyomas, germline testing revealed normal FH status in five (unsuccessful in the sixth). Similarly Miettinen et al 38 reported that 5% of the uterine smooth muscle tumors analyzed (n=1583) were FH-deficient by immunohistochemistry with most (79%) being leiomyomas with bizarre nuclei. They noted that while similar histologic features were often seen in both FH-deficient and FH-proficient leiomyomas with bizarre nuclei those that were FH-deficient were more likely to have staghorn vessels, prominent eosinophilic nucleoli, and perinucleolar halos.…”
Section: Discussionmentioning
confidence: 82%
“…Although molecular studies on leiomyomas with an aberrant immunoprofile are limited, especially those implementing germline testing, data thus far favors these tumors to harbor somatic mutations. 36 , 38 , 40 In a series of 194 leiomyomas from patients less than 40 years, Joseph et al 40 identified five tumors that were 2SC-positive (two of them completely FH-negative), and four of these were classified as “highly suspicious for hereditary leiomyomatosis and renal cell carcinoma syndrome” based upon morphology. Molecular analysis identified somatic mutations in four leiomyomas and homozygous deletion of the FH gene in the other, but germline testing was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Einige der zahlreichen Leiomyomvarianten verdienen eine genauere Betrachtung [10] [12]. Diese Knoten, die sich meist bei jungen Frauen finden, weisen oft eine deutliche Kernpolymorphie und einen erhöhten Zellreichtum auf, wobei differenzialdiagnostisch Leiomyome mit bizarren Zellkernen im Raum stehen (.…”
Section: Leiomyomvariantenunclassified
“…FH-defiziente Leiomyome finden sich in etwa 0,4-1,6 % aller nichtselektierten Leiomyome ohne Atypien sowie in 1,8 % aller zellreichen Leiomyome und etwa einem Drittel aller Leiomyome mit bizarren Zellkernen [13]. Eine FH-Defizienz konnte bis dato hingegen noch nicht in Leiomyosarkomen nachgewiesen werden [12].…”
Section: Leiomyomvariantenunclassified